2017
DOI: 10.1038/s41598-017-06876-8
|View full text |Cite
|
Sign up to set email alerts
|

Early functional network alterations in asymptomatic elders at risk for Alzheimer’s disease

Abstract: Amyloid-β (Aβ) deposition is known to starts decades before the onset of clinical symptoms of Alzheimer’s disease (AD), however, the detailed pathophysiological processes underlying this preclinical period are not well understood. This study aimed to investigate functional network alterations in cognitively intact elderly individuals at risk for AD, and assessed the association between these network alterations and changes in Aβ deposition, glucose metabolism, and brain structure. Forty-five cognitively normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 54 publications
3
69
0
Order By: Relevance
“…Such voxel-based comparison of each patient's FDG-PET data with that of those of the healthy elders' group was not performed in the present study due to (i) the low number of healthy elders and the need to have a large group of healthy subjects (>50) to increase the sensitivity/specificity of such highly multivariate FDG-PET analyses 93 , and (ii) because of the high-resolution and MRI-based correction for attenuation of our FDG-PET data, which complicate the use of FDG-PET data available in large database (e.g., ADNI). Furthermore, a previous study has shown that healthy elders at risk for AD (i.e., with Aβ-positive defined by using C-Pittsburgh compound B PET), contrary to healthy elders with Aβ-negative, presented an increase in rsFC between the precuneus and the bilateral inferior parietal lobules in theta and delta frequency bands 94 . This finding suggests an association between these electrophysiological rsFC changes and local cerebral amyloid deposition 94 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such voxel-based comparison of each patient's FDG-PET data with that of those of the healthy elders' group was not performed in the present study due to (i) the low number of healthy elders and the need to have a large group of healthy subjects (>50) to increase the sensitivity/specificity of such highly multivariate FDG-PET analyses 93 , and (ii) because of the high-resolution and MRI-based correction for attenuation of our FDG-PET data, which complicate the use of FDG-PET data available in large database (e.g., ADNI). Furthermore, a previous study has shown that healthy elders at risk for AD (i.e., with Aβ-positive defined by using C-Pittsburgh compound B PET), contrary to healthy elders with Aβ-negative, presented an increase in rsFC between the precuneus and the bilateral inferior parietal lobules in theta and delta frequency bands 94 . This finding suggests an association between these electrophysiological rsFC changes and local cerebral amyloid deposition 94 .…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a previous study has shown that healthy elders at risk for AD (i.e., with Aβ-positive defined by using C-Pittsburgh compound B PET), contrary to healthy elders with Aβ-negative, presented an increase in rsFC between the precuneus and the bilateral inferior parietal lobules in theta and delta frequency bands 94 . This finding suggests an association between these electrophysiological rsFC changes and local cerebral amyloid deposition 94 . Further research should investigate the dynamic resting-state changes in healthy elders at risk of developing AD in order to clarify the relation with AD pathology.…”
Section: Discussionmentioning
confidence: 96%
“…Early loss of inhibitory neurons in preclinical AD leads to a state of increased hyperexcitability and hypersynchrony [13][14][15], which has been found to augment amyloid release and produce neurotoxic effects [16,17]. We hypothesize that PA exerts a neuroprotective effect that will be associated with reduced network synchrony in both groups, in opposition to the state of synaptic hyperexcitability that characterizes preclinical and prodromal AD [18][19][20][21][22]. Then, once we have identified the functional connectivity (FC) patterns that are influenced by PA level, we will explore if there are any associations between these FC patterns and structural integrity (gray and white matter), cognition, and mood.…”
Section: Introductionmentioning
confidence: 97%
“…Artifact-free data were segmented in 4 seconds epochs. Then MEG time series were filtered into delta (2-4Hz), theta (4-8Hz), alpha (8-12Hz) and beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). This procedure has been reported in detailed in (22).…”
Section: Magnetoencephalographymentioning
confidence: 99%
“…Early loss of inhibitory neurons in preclinical AD leads to a state of increased hyperexcitability and hypersynchrony (13)(14)(15), which has been found to augment amyloid release and produce neurotoxic effects (16,17). We hypothesize that PA exerts a neuroprotective effect that will be associated with reduced network synchrony in both groups, in opposition to the state of synaptic hyperexcitability that characterizes preclinical and prodromal AD (18)(19)(20)(21)(22). Then, once we have identified the functional connectivity (FC) patterns that are influenced by PA level, we will explore if there are any associations between these FC patterns and structural integrity (grey and white matter), cognition, and mood.…”
mentioning
confidence: 99%